Multigene assays in early breast cancer: Insights from recent phase 3 studies. Issue 4 (April 2020) - Markopoulos, C.; Hyams, D.M.; Gomez, H.L.; Harries, M.; Nakamura, S.; Traina, T.; Katz, A.
Abstract: Multigene assays (MGAs) guide treatment in early-stage breast cancer (ESBC) enabling selective and effective use of adjuvant chemotherapy (CT). Support for all MGAs had previously been derived from retrospectively-analyzed, prospective studies. Only 2 ESBC MGAs, the 70-gene signature (MammaPrint®) and the 21-gene Recurrence Score (RS) assay (Oncotype DX®), are now supported by entirely prospective randomized phase 3 trials. These studies varied in their primary objectives, design, and eligibility. The MINDACT study provided the first level 1 evidence for the 70-gene signature, identifying a prognostic capability irrespective of lymph node (LN) or hormone receptor (HR) status. However, the study did not support predictive value for the assay regarding adjuvant CT utility. The second prospective study, WSG-PlanB, confirmed the prognostic value of the 21-gene RS assay in HR-positive tumors with RS ≤ 11. A 5-year disease free survival (DFS) of 94% was identified in this group when treated with endocrine therapy (ET) alone regardless of N0 or N1 nodal status. The final new prospective study, TAILORx, confirmed the prognostic value of the 21-gene assay in N0 HR-positive disease, demonstrating a lack of CT benefit in patients with midrange RS. The information from these phase 3 studies confirms that MGAs are not interchangeable and that each provides different information for differing patient populations. Prognosis-only is supported for the 70-gene signature while both prognosis and the predictive value of CT are provided by the 21-gene assay. This review assesses and contrasts these phase 3 studies in the context of target populations and clinical utility.